2007
DOI: 10.1186/bcr1781
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and breast density in high-risk women: a cross-sectional study

Abstract: Background Women with a family history of breast cancer may be at higher risk for breast cancer, but few previous studies evaluating diet and breast cancer have focused on such women. The objective of the present study was to determine whether diet, a modifiable risk factor, is related to breast density among women at high genetic risk for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 39 publications
4
62
0
Order By: Relevance
“…Indeed, in our data, saturated fat and unsaturated fat intakes, such as mono- and polyunsaturated fat, particularly from long-chain omega-3 fat, had opposing associations with %DBV. Our significant positive association of saturated fat with %DBV is consistent with three studies (46, 48, 62), although others have reported no associations (47, 50, 52) or significant inverse associations (53). Contrary to the inverse associations we observed with unsaturated fat intake, most studies of adult women found no significant association between breast density and intakes of monounsaturated fat (47, 48, 50, 53, 62), polyunsaturated fat (4648, 50, 53), or omega-3 fat (48), while one found significant positive association with monounsaturated fat (49).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in our data, saturated fat and unsaturated fat intakes, such as mono- and polyunsaturated fat, particularly from long-chain omega-3 fat, had opposing associations with %DBV. Our significant positive association of saturated fat with %DBV is consistent with three studies (46, 48, 62), although others have reported no associations (47, 50, 52) or significant inverse associations (53). Contrary to the inverse associations we observed with unsaturated fat intake, most studies of adult women found no significant association between breast density and intakes of monounsaturated fat (47, 48, 50, 53, 62), polyunsaturated fat (4648, 50, 53), or omega-3 fat (48), while one found significant positive association with monounsaturated fat (49).…”
Section: Discussionsupporting
confidence: 91%
“…Genetics, environment, as well as dietary factors such as vitamin D are thought to play significant roles in breast cancer risk (2). For example, epidemiological evidence suggests that increased sun exposure as well as increased dietary vitamin D intake, are correlated with decreased breast cancer incidence (35). Further, low levels of circulating 25(OH)D, an indicator of vitamin D status, are associated with high breast cancer risk (6) and results from the Women’s Health Initiative shows that women who consumed calcium and vitamin D supplements have lower incidence of breast carcinoma in situ (7).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized control trials demonstrated changes in breast density with intake of low-fat high carbohydrate diet. 70,71 Cross-sectional studies have shown calcium and vitamin D, [72][73][74][75][76] and vegetables 75,77 to be associated with lower breast density.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%